Colloidal FAPbBr3 perovskite nanocrystals for light emission: what's going on?. Issue 37 (14th June 2022) - Bhatia, Harshita; Ghosh, Biplab; Debroye, Elke
Abstract : This review summarizes the current prospect of FAPbBr3 nanocrystals – from synthesis to applications in light emitting diodes and highlights the challenges and promising strategies to mitigate the concerns. Abstract : Semiconducting nanomaterials have been widely explored in diverse optoelectronic applications. Colloidal lead halide perovskite nanocrystals (NCs) have recently been an excellent addition to the field of nanomaterials, promising an enticing building block in the field of light emission. In addition to the notable optoelectronic properties of perovskites, the colloidal NCs exhibit unique size-dependent optical properties due to the quantum size effect, which makes them highly attractive for light-emitting diodes (LEDs). In the past few years, perovskite-based LEDs (PeLEDs) have demonstrated a meteoritic rise in their external quantum efficiency (EQE) values, reaching over 20% so far. Among various halide perovskite compositions, FAPbBr3 and its variants remain one of the most interesting and sought-after compounds for green light emission. This review focuses on recent progress in the design and synthesis protocols of colloidal FAPbBr3 NCs and the emerging concepts in tailoring their surface chemistry. The structural and physicochemical features of lead halide perovskites along with a comprehensive discussion on their defect-tolerant properties are briefly outlined. Later, the prevalent synthesis, ligand, and compositional engineering strategies to boost the stability and photoluminescence quantum yield (PLQY) of FAPbBr3 NCs are extensively discussed. Finally, the fundamental concepts and recent progress on FAPbBr3 -based LEDs, followed by a discussion of the challenges and prospects that are on the table for this enticing class of perovskites, are reviewed.